Do leadership training and aevelopment make a difference in the public sector? a panel study - Seidle, Brett; Fernandez, Sergio; Perry, James L. (2016)
Although significant progress has been made in developing leadership theory and understanding the traits, skills, behaviors, and styles that make a good leader, progress in bridging the gap between theory and practice using models of leadership training and development has been slow. This research attempts to answer the question of whether leadership training and development programs in the public sector improve leader and organizational performance. The findings indicate that a combination of coaching, classroom instruction, feedback, and experiential training has a significant impact on leader performance. In addition, organizational effectiveness improves for organizations whose leaders received the intervention. This article enhances our understanding of the impact that training and development can have on leader and organizational outcomes. - Reproduced.
Keywords: Public administration; Training; Leadership